2013
DOI: 10.1063/1.4822433
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond pulse generation in passively mode locked InAs quantum dot lasers

Abstract: Optical pulse durations of an InAs two-section passively mode-locked quantum dot laser with a proton bombarded absorber section reduce from 8.4 ps at 250K to 290 fs at 20 K, a factor of 29, with a corresponding increase in optical bandwidth. Rate equation analysis of gain and emission spectra using rate equations suggests this is due to the very low emission rate of carriers to the wetting layer in the low temperature, random population regime which enables dots across the whole inhomogeneous distribution to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…3 at 80 K since these were single pass measurements in the absence of lasing [12]. At 80 K, the calculated escape rates from the dots to the wetting layer becomes very slow so the model no longer predicts a Fermi-Dirac distribution [9].…”
Section: Rate Equation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…3 at 80 K since these were single pass measurements in the absence of lasing [12]. At 80 K, the calculated escape rates from the dots to the wetting layer becomes very slow so the model no longer predicts a Fermi-Dirac distribution [9].…”
Section: Rate Equation Analysismentioning
confidence: 99%
“…We have previously shown that the pulsewidths of mode-locked quantum dot devices decrease with decreasing temperature and at 20 K pulsewidths of 300 fs have been achieved using a proton bombarded absorber section [9].…”
mentioning
confidence: 99%
“…In particular, MLLs based on semiconductor quantum-dash (Q-Dash) and quantum-dot (QD) materials have attracted profuse research effort, as these offer very large bandwidths, lower threshold current densities and excellent temperature performance making them of great interest for use in ultrafast optical systems (see 18 , 19 for reviews). In recent years, the technology has developed rapidly and QDMLLs with repetition rates up to hundreds of GHz 20 , yielding ultrashort pulse durations 21 , 22 (down to femtosecond regimes), and offering stable mode-locking for wide temperature ranges (up to >100 C) have been reported 23 , 24 . The effect of external optical injection in QDMLLs has also undergone substantial research effort recently 25 30 .…”
Section: Introductionmentioning
confidence: 99%
“…5 It has recently been demonstrated that random occupation in QD systems can improve mode locked laser performance where pulse widths as short as 290 fs were observed from a QD sample at 20 K, believed to be operating in the random regime. 6 The evidence for random occupancy on the dots was provided by fitting model calculations to the radiative threshold current of the laser. Dual wavelength lasing is currently of particular interest 7 due to its applications including terahertz generation, 8 but at present the carrier competition between the QD states is considered to be a significant limiting factor.…”
mentioning
confidence: 99%